Серебряная лодка: стихи и поэмы : перевод с удмуртского / Николай Байтеряков - Байтеряков Николай Семенович (Удмуртия, 1989)
Экземпляры: (20240227) / Инвентарный номер: 22735 / Цена: 1.00 / Сис.шифр: Р2 / Авт.знак: Б 18 / ГРНТИ: 17.82.10 / ББК: 84(2Рос=Удм)